Do Need-Supportive Teaching Practices and Student-Perceived Need Fulfillment Matter Academic Achievement? The Mediating of Anxiety and Educational Opportunities in Indonesia - Maunah, Binti (Asian Journal of Multidisciplinary Studies, 2024)
This study examines the relationships between need-supportive teaching practices, student-perceived need fulfillment, anxiety, educational opportunities, and academic achievement in low socioeconomic status high schools in Indonesia. Data were collected through surveys and interviews from a diverse sample of high school students. Path analysis and mediation analyses were conducted. Results indicate that need-supportive teaching practices positively correlate with student-perceived need fulfillment, which, in turn, positively influences academic achievement. Anxiety and educational opportunities were found to mediate the relationship between need-supportive teaching practices, student-perceived need fulfillment, and academic achievement, underscoring the hindrance of high anxiety levels on academic performance. Furthermore, educational opportunities were identified as a significant mediator, highlighting the importance of equitable access to quality education. These findings contribute to the understanding of the role of need-supportive teaching practices, student needs, anxiety, and educational opportunities in academic achievement. The study suggests the implementation of strategies that promote supportive teaching, address student anxiety, and provide equal educational opportunities to enhance academic success. Limitations include the study's specific context, sample size, and generalizability. Future research should consider diverse contexts, larger samples, longitudinal designs, and objective measures of academic achievement.